Preparation method of oxygen-free copper
Through gradient smelting deoxygenation, gradient refining treatment and directional solidification casting, combined with ultrasonic vibration and composite deoxidant, the problem of difficulty in reducing the oxygen content in the preparation of oxygen-free copper is solved, and efficient and low-cost production of oxygen-free copper is achieved, which improves mechanical mechanics and electrical conductivity.
Patent Information
- Application Number
- CN202510752101.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-06
- Publication Date
- 2025-08-12
- Estimated Expiration
- 2045-06-06
AI Technical Summary
The existing oxygen-free copper preparation methods have problems such as poor production continuity, high energy consumption, high equipment costs and difficulty in further reducing oxygen content, resulting in insufficient mechanical and mechanical properties, conductive properties and heat resistance.
The process flow of gradient smelting deoxygenation, gradient refining treatment, directional solidification casting and heat treatment is adopted, combined with ultrasonic vibration, composite deoxidant and pulsed magnetic field, and the addition of deoxidant is achieved through ultrasonic cavitation effect, gas flotation principle and precise control of the amount of deoxidant added, so as to achieve efficient deoxidation and impurity removal.
It has achieved efficient preparation of oxygen-free copper, good mechanical and mechanical properties, good conductivity and heat resistance, low oxygen content, and is suitable for continuous large-scale production.
Smart Images

Figure SMS_6
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of metallurgy, and in particular to a method for preparing oxygen-free copper. Background Art
[0002] Oxygen-free copper (Oxygen-free copper) is widely used in electronics, information technology, high-end electrical appliances, and other fields due to its excellent electrical and thermal conductivity, as well as good processing properties. With technological advancements, the purity and performance requirements for Oxygen-free copper are becoming increasingly demanding. While traditional Oxygen-free copper preparation methods can achieve low oxygen content, they suffer from issues such as poor production continuity, high energy consumption, and high equipment costs, making them difficult to meet the requirements of high-end applications.
[0003] Existing methods for preparing oxygen-free copper mainly include electrolytic refining and vacuum melting. Although electrolytic refining can improve the purity of copper to a certain extent, the control of the electrolyte composition during the preparation process is relatively complex and easily introduces other impurities, making it difficult to further reduce the oxygen content of the final product. The vacuum melting method is to melt copper in a vacuum environment to reduce the involvement of oxygen. However, this method has extremely high requirements for equipment, the vacuum degree is difficult to control, and the copper liquid easily reacts with containers such as crucibles during the smelting process, introducing other impurity elements. At the same time, vacuum melting takes a long time and has high production costs, which is not conducive to large-scale production. Other previously disclosed methods for preparing oxygen-free copper also have more or less technical defects such as insufficiently precise control of the oxygen content during the preparation process, making it difficult to prepare high-purity, high-performance oxygen-free copper, and low production efficiency and high costs.
[0004] To address the above-mentioned issues, a Chinese invention patent with authorization publication number CN114150179B discloses an oxygen-free copper material, an oxygen-free copper material product, and a preparation method thereof, comprising the following steps: 1) refining a copper liquid; wherein the composition of the copper liquid satisfies the following requirements: O≤0.0005wt%; P≤0.001wt%; Fe≤0.001wt%; S≤0.001wt%; and the total content of Pb, As, Bi, Sb, Zn, Sn, and Ni≤0.0001wt%; 2) transferring the copper liquid to a casting furnace, adding a copper-rare earth master alloy thereto, and then performing a casting process to obtain an oxygen-free copper material; wherein the amount of the copper-rare earth master alloy added satisfies the following requirements: the mass of the rare earth is 0.01-0.02wt% of the mass of the copper liquid; and wherein the mass fraction of the rare earth in the copper-rare earth master alloy is 15-25wt%. However, the oxygen content of oxygen-free copper produced by this preparation method needs to be further reduced, and the electrical conductivity, heat resistance and mechanical properties still need to be further improved.
[0005] It can be seen that developing a preparation method for oxygen-free copper with good mechanical properties, excellent electrical conductivity and heat resistance, and low oxygen content meets market demand, has broad market value and application prospects, and is of great significance to promoting the development of the oxygen-free copper field. Summary of the Invention
[0006] The purpose of the present invention is to overcome the deficiencies of the prior art and to provide a method for preparing oxygen-free copper with good mechanical properties, good electrical conductivity and heat resistance and low oxygen content.
[0007] To achieve the above object, the technical solution adopted by the present invention is: a method for preparing oxygen-free copper, comprising the following steps: Step S1, raw material pretreatment: placing the electrolytic copper raw material in a vacuum baking furnace for preheating for 1-2 hours to remove adsorbed water and volatile impurities; taking it out and cooling it to room temperature, sandblasting the surface oxide layer, ultrasonically cleaning it with ethanol, and then drying it with nitrogen to obtain the copper material; Step S2, gradient melting and deoxidation: in a reducing gas atmosphere, add the copper material to a graphite crucible and melt it at 1200-1220°C at a rate of 5-8°C / min; after it is completely melted, start the ultrasonic vibration system and add titanium magnesium zirconium deoxidizer at the same time, and ultrasonic vibration deoxidize for 30-40 minutes. During the vibration process, argon gas with a flow rate of 4-6 L / min is introduced simultaneously; then cover the composite deoxidizer, and bottom blow argon gas with a flow rate of 15-20 L / min to strengthen deoxidation for 15-20 minutes; finally, transfer it to a holding furnace at 1150-1200°C and introduce argon gas with a flow rate of 1-5 L / min. Deoxygenate again for 20-30 minutes; Step S3, gradient refining treatment: After deoxidation, a composite refining agent is added to the copper liquid, and the copper liquid is refined at 1100-1150°C for 10-15 minutes. Then, red phosphorus is added and the copper liquid is refined at 1140-1160°C for 8-12 minutes. Finally, the temperature is lowered to 1090-1110°C, a phosphorus-copper master alloy is added, and a pulsed magnetic field is applied. The copper liquid is further refined for 5-8 minutes, and then the slag is skimmed and filtered using a ceramic filter. Step S4, directional solidification casting: Directional solidification casting is performed using a bottom-draw continuous casting machine, with the molten copper passing through a water-cooled copper mold at a speed of 100-120 mm / min. A gradient cooling zone is set in the mold to achieve directional growth of columnar crystals, thereby obtaining an oxygen-free copper ingot; Step S5, heat treatment: placing the oxygen-free copper ingot into an annealing furnace, heating it to 450-550° C. at a heating rate of 3-5° C. / min under nitrogen protection, keeping the temperature for 1-3 hours, and then cooling it to room temperature along with the furnace.
[0008] Preferably, the purity of the electrolytic copper raw material in step S1 is ≥99.99%.
[0009] Preferably, the preheating temperature in step S1 is 240-255°C and the vacuum degree is 1×10 -3 Pa.
[0010] Preferably, the reducing gas in step S2 is a mixture of carbon monoxide and argon in a volume ratio of 3:17.
[0011] Preferably, the ultrasonic vibration system in step S2 has an amplitude of 14-16 μm, a frequency of 19.5-20.5 kHz, and a power of 1-3 kW.
[0012] Preferably, the mass ratio of Ti, Mg and Zr in the titanium magnesium zirconium deoxidizer in step S2 is 3:1:0.5.
[0013] Preferably, the amount of the titanium magnesium zirconium deoxidizer added in step S2 is 0.05-0.07% of the mass of the copper material.
[0014] Preferably, the covering thickness of the composite deoxidizer in step S2 is 180-200 mm.
[0015] Preferably, the composite deoxidizer in step S2 comprises the following components in parts by weight: 85-90 parts of calcined charcoal, 5-8 parts of calcium fluoride, 3-5 parts of calcium oxide, 1-2 parts of boron oxide, and 1-3 parts of calcium boride.
[0016] Preferably, the mass ratio of the composite refining agent, red phosphorus, phosphorus-copper master alloy, and copper liquid in step S3 is (0.01-0.02):0.03:0.02:100.
[0017] Preferably, the mass percentage concentration of phosphorus in the phosphorus-copper master alloy in step S3 is 10-15%.
[0018] Preferably, the composite refining agent in step S3 comprises the following components in parts by weight: 2-4 parts of mixed rare earth, 0.3-0.6 parts of boron powder, 0.1-0.3 parts of magnesium, and 4-6 parts of calcium fluoride.
[0019] Preferably, the mixed rare earth is a mixture of neodymium, yttrium, cerium and lanthanum in a mass ratio of (5-8):(2-4):(1-3):(3-5).
[0020] Preferably, the magnetic field strength of the pulsed magnetic field in step S3 is 5 T, the pulse frequency is 10 Hz, and the duty cycle is 60%.
[0021] Preferably, in step S4, the upper temperature of the gradient cooling zone is 1180° C., and the lower temperature is 1050° C.; the cooling rate is maintained at 15-20° C. / min.
[0022] Preferably, the crystallizer of the bottom-draw continuous casting machine in step S4 is made of a water-cooled copper mold, the crystallizer water pressure is 0.28-0.35 MPa, and the cooling water flow rate is 9-11 m³ / h.
[0023] Due to the application of the above technical solution, the present invention has the following beneficial effects: (1) The preparation method of oxygen-free copper disclosed in the present invention has a short process flow, high speed, low energy consumption, low dependence on equipment, high preparation efficiency and yield rate, is suitable for continuous large-scale production, and has high promotion and application value.
[0024] (2) The preparation method of oxygen-free copper disclosed in the present invention adopts gradient staged smelting deoxidation, which can not only effectively remove dissolved oxygen, but also selectively remove interstitial oxygen, so that the oxygen content in the oxygen-free copper product is significantly reduced, thereby effectively improving the mechanical properties, electrical conductivity and heat resistance of the product; the ultrasonic cavitation effect and gas flotation principle are introduced into the preparation of oxygen-free copper to form a "sound-gas-solid" three-phase synergistic deoxidation mechanism. The periodic pressure changes generated by ultrasound in the copper liquid will cause microcracks on the surface of nano-scale oxide inclusions, exposing active sites and promoting the adsorption reaction of deoxidizing elements. At the same time, the local high temperature generated when the cavitation bubble collapses reduces the oxide on the inclusion surface, and the released oxygen atoms form stable compounds with the deoxidizer; argon bubbles serve as a capture carrier for inclusions, and the wake effect generated during their ascent will drive the inclusion movement, while the acoustic flow effect of ultrasound can enhance the collision probability of inclusions and bubbles, thereby further reducing the oxygen content. The active ingredients in the titanium magnesium zirconium deoxidizer have a strong affinity with oxygen and can quickly react with oxygen in the copper liquid to generate Stable oxides such as MgO, ZrO, and ZrO have low density and easily float to the surface of the copper solution, where they can be removed. By precisely controlling the amount of deoxidizer added, as well as the temperature and time of deoxidation, the oxygen content is precisely controlled, significantly reducing the oxygen content of oxygen-free copper. A reducing gas atmosphere is used to penetrate the melt at high temperatures, directly reducing dissolved oxygen and further reducing the oxygen content.
[0025] (3) The composite deoxidizer disclosed in the present invention comprises the following components, measured in parts by weight: 85-90 parts of calcined charcoal, 5-8 parts of calcium fluoride, 3-5 parts of calcium oxide, 1-2 parts of boron oxide, and 1-3 parts of calcium boride. By rationally selecting the above components, the oxygen content of the product can be further reduced. This, in conjunction with other process parameters, results in an oxygen-free copper product having excellent mechanical properties, electrical conductivity, and heat resistance.
[0026] (4) The preparation method of oxygen-free copper disclosed in the present invention adopts gradient refining treatment, and the composite refining agent includes the following components in parts by weight: 2-4 parts of mixed rare earth, 0.3-0.6 parts of boron powder, 0.1-0.3 parts of magnesium, and 4-6 parts of calcium fluoride. Through the coordinated action of the various components of the refining agent, further deoxidation and impurity removal can be achieved, improving the microstructure and performance, which is beneficial to improving product quality. The pulsed magnetic field synergistically improves the efficiency of inclusion removal; through the reasonable selection of various parameters of the gradient refining process, it is possible to achieve a dual reduction in oxygen content and total impurity content; and the conductive and mechanical properties are synergistically optimized.
[0027] (5) The preparation method of oxygen-free copper disclosed in the present invention adopts a directional solidification casting process, which can effectively improve the electrical conductivity, mechanical properties and high-temperature stability of the product. DETAILED DESCRIPTION
[0028] The following description is intended to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are merely examples, and those skilled in the art may conceive of other obvious variations. Example 1
[0029] A method for preparing oxygen-free copper comprises the following steps: Step S1, raw material pretreatment: placing the electrolytic copper raw material in a vacuum baking furnace for preheating for 1 hour to remove adsorbed water and volatile impurities; taking it out and cooling it to room temperature, sandblasting the surface oxide layer, ultrasonically cleaning it with ethanol, and then drying it with nitrogen to obtain the copper material; Step S2, gradient melting and deoxidation: In a reducing gas atmosphere, the copper material is added to a graphite crucible and heated to 1200°C at a rate of 5°C / min to melt; after complete melting, the ultrasonic vibration system is started, and a titanium magnesium zirconium deoxidizer is added at the same time, and ultrasonic vibration deoxidation is carried out for 30 minutes, and argon gas at a flow rate of 4 L / min is introduced during the vibration process; then, the composite deoxidizer is covered, and argon gas at a flow rate of 15 L / min is blown from the bottom to enhance deoxidation for 15 minutes; finally, the copper material is transferred to a holding furnace at 1150°C, and CO2 at a flow rate of 1 L / min is introduced for further deoxidation for 20 minutes; Step S3, gradient refining treatment: After deoxidation, a composite refining agent is added to the copper liquid, and the copper liquid is refined at 1100°C for 10 minutes. Then, red phosphorus is added and the copper liquid is refined at 1140°C for 8 minutes. Finally, the temperature is lowered to 1090°C, a phosphorus-copper master alloy is added, and a pulsed magnetic field is applied. After further refining for 5 minutes, the copper liquid is skimmed and filtered using a ceramic filter. Step S4, directional solidification casting: Directional solidification casting is performed using a bottom-draw continuous casting machine, with the molten copper passing through a water-cooled copper mold at a speed of 100 mm / min. A gradient cooling zone is set in the mold to achieve directional growth of columnar crystals, thereby obtaining an oxygen-free copper ingot; Step S5, heat treatment: placing the oxygen-free copper ingot into an annealing furnace, heating it to 450° C. at a heating rate of 3° C. / min under nitrogen protection, keeping the temperature for 1 hour, and then cooling it to room temperature along with the furnace.
[0030] The purity of the electrolytic copper raw material in step S1 is ≥99.99%; the preheating temperature in step S1 is 240°C and the vacuum degree is 1×10 -3 Pa; the reducing gas in step S2 is a mixture of carbon monoxide and argon in a volume ratio of 3:17; the amplitude of the ultrasonic vibration system in step S2 is 14 μm, the frequency is 19.5 kHz, and the power is 1 kW; the mass ratio of Ti, Mg, and Zr in the titanium magnesium zirconium deoxidizer in step S2 is 3:1:0.5; the amount of the titanium magnesium zirconium deoxidizer added in step S2 is 0.05% of the mass of the copper material; the covering thickness of the composite deoxidizer in step S2 is 180 mm.
[0031] The composite deoxidizer in step S2 includes the following components in parts by weight: 85 parts of calcined charcoal, 5 parts of calcium fluoride, 3 parts of calcium oxide, 1 part of boron oxide, and 1 part of calcium boride; the mass ratio of the composite refining agent, red phosphorus, phosphorus-copper master alloy, and copper liquid in step S3 is 0.01:0.03:0.02:100; the mass percentage concentration of phosphorus in the phosphorus-copper master alloy in step S3 is 10%; the composite refining agent in step S3 includes the following components in parts by weight: The following components are prepared in parts by weight: 2 parts of mixed rare earth, 0.3 parts of boron powder, 0.1 parts of magnesium, and 4 parts of calcium fluoride; the mixed rare earth is a mixture of neodymium, yttrium, cerium, and lanthanum in a mass ratio of 5:2:1:3; the magnetic field strength of the pulsed magnetic field in step S3 is 5 T, the pulse frequency is 10 Hz, and the duty cycle is 60%; the upper temperature of the gradient cooling zone in step S4 is 1180° C., and the lower temperature is 1050° C.; and the cooling rate is maintained at 15° C. / min.
[0032] The crystallizer of the bottom-draw continuous casting machine in step S4 is made of a water-cooled copper mold, the crystallizer water pressure is 0.28 MPa, and the cooling water flow rate is 9 m³ / h. Example 2
[0033] A method for preparing oxygen-free copper comprises the following steps: Step S1, raw material pretreatment: placing the electrolytic copper raw material in a vacuum baking furnace for preheating for 1.2 hours to remove adsorbed water and volatile impurities; taking it out and cooling it to room temperature, sandblasting the surface oxide layer, ultrasonically cleaning it with ethanol, and then drying it with nitrogen to obtain the copper material; Step S2, gradient melting and deoxidation: In a reducing gas atmosphere, the copper material is added to a graphite crucible and heated to 1205°C at 6°C / min to melt; after it is completely melted, the ultrasonic vibration system is started, and a titanium magnesium zirconium deoxidizer is added at the same time, and ultrasonic vibration deoxidation is carried out for 33 minutes. During the vibration process, argon gas with a flow rate of 4.5 L / min is introduced simultaneously; then the composite deoxidizer is covered, and argon gas with a flow rate of 16 L / min is blown at the bottom to strengthen deoxidation for 17 minutes; finally, the copper material is transferred to a holding furnace at 1170°C and a flow rate of 2 L / min is introduced. Deoxygenation was performed again for 23 min; Step S3, gradient refining treatment: After deoxidation, a composite refining agent is added to the copper liquid, and the copper liquid is refined at 1120°C for 12 minutes. Then, red phosphorus is added and the copper liquid is refined at 1145°C for 9 minutes. Finally, the temperature is lowered to 1095°C, a phosphorus-copper master alloy is added, and a pulsed magnetic field is applied. After refining for another 6 minutes, the copper liquid is skimmed and filtered using a ceramic filter. Step S4, directional solidification casting: Directional solidification casting is performed using a bottom-draw continuous casting machine, with the molten copper passing through a water-cooled copper mold at a speed of 105 mm / min. A gradient cooling zone is set in the mold to achieve directional growth of columnar crystals, thereby obtaining an oxygen-free copper ingot; Step S5, heat treatment: placing the oxygen-free copper ingot into an annealing furnace, heating it to 480° C. at a heating rate of 3.5° C. / min under nitrogen protection, keeping the temperature for 1.5 hours, and then cooling it to room temperature along with the furnace.
[0034] The purity of the electrolytic copper raw material in step S1 is ≥99.99%; the preheating temperature in step S1 is 245°C and the vacuum degree is 1×10 -3 Pa; the reducing gas in step S2 is a mixture of carbon monoxide and argon in a volume ratio of 3:17; the amplitude of the ultrasonic vibration system in step S2 is 14.5 μm, the frequency is 20 kHz, and the power is 1.5 kW; the mass ratio of Ti, Mg, and Zr in the titanium magnesium zirconium deoxidizer in step S2 is 3:1:0.5; the addition amount of the titanium magnesium zirconium deoxidizer in step S2 is 0.055% of the mass of the copper material; the covering thickness of the composite deoxidizer in step S2 is 185 mm; the composite deoxidizer in step S2 comprises the following components in parts by weight: 87 parts of calcined charcoal, 6 parts of calcium fluoride, 3.5 parts of calcium oxide, 1.2 parts of boron oxide, and 1.5 parts of calcium boride; the mass ratio of the composite refining agent, red phosphorus, phosphorus-copper master alloy, and copper liquid in step S3 is 0.013:0.03:0.02:100.
[0035] The mass percentage concentration of phosphorus in the phosphorus-copper master alloy in step S3 is 12%; the composite refining agent in step S3 includes the following components, measured in parts by weight: 2.5 parts of mixed rare earth, 0.4 parts of boron powder, 0.15 parts of magnesium, and 4.5 parts of calcium fluoride; the mixed rare earth is a mixture of neodymium, yttrium, cerium, and lanthanum in a mass ratio of 6:2.5:1.5:3.5; the magnetic field strength of the pulsed magnetic field in step S3 is 5 T, the pulse frequency is 10 Hz, and the duty cycle is 60%; the upper temperature of the gradient cooling zone in step S4 is 1180° C., and the lower temperature is 1050° C.; the cooling rate is maintained at 17° C. / min; the crystallizer of the bottom-draw continuous casting machine in step S4 is made of a water-cooled copper mold, the crystallizer water pressure is 0.3 MPa, and the cooling water flow rate is 9.5 m³ / h. Example 3
[0036] A method for preparing oxygen-free copper comprises the following steps: Step S1, raw material pretreatment: placing the electrolytic copper raw material in a vacuum baking furnace for preheating for 1.5 hours to remove adsorbed water and volatile impurities; taking it out and cooling it to room temperature, sandblasting the surface oxide layer, ultrasonically cleaning it with ethanol, and then drying it with nitrogen to obtain the copper material; Step S2, gradient melting and deoxidation: in a reducing gas atmosphere, add the copper material to a graphite crucible and melt it at 6.5°C / min to 1210°C; after it is completely melted, start the ultrasonic vibration system and add titanium magnesium zirconium deoxidizer at the same time, and ultrasonic vibration deoxidize for 35 minutes. During the vibration process, argon gas with a flow rate of 5L / min is introduced simultaneously; then cover the composite deoxidizer, and bottom blow argon gas with a flow rate of 18L / min to strengthen deoxidation for 18 minutes; finally, transfer it to a holding furnace at 1180°C and introduce argon gas with a flow rate of 3L / min. Deoxygenate again for 25 min; Step S3, gradient refining treatment: After deoxidation, a composite refining agent is added to the copper liquid, and the copper liquid is refined at 1130°C for 13 minutes. Then, red phosphorus is added and the copper liquid is refined at 1150°C for 10 minutes. Finally, the temperature is lowered to 1100°C, a phosphorus-copper master alloy is added, and a pulsed magnetic field is applied. The copper liquid is further refined for 6.5 minutes, and then the slag is skimmed and filtered using a ceramic filter. Step S4, directional solidification casting: Directional solidification casting is performed using a bottom-draw continuous casting machine, with the molten copper passing through a water-cooled copper mold at a speed of 110 mm / min. A gradient cooling zone is set in the mold to achieve directional growth of columnar crystals, thereby obtaining an oxygen-free copper ingot; Step S5, heat treatment: placing the oxygen-free copper ingot into an annealing furnace, heating it to 500° C. at a heating rate of 4° C. / min under nitrogen protection, keeping the temperature for 2 hours, and then cooling it to room temperature along with the furnace.
[0037] The purity of the electrolytic copper raw material in step S1 is ≥99.99%; the preheating temperature in step S1 is 249°C and the vacuum degree is 1×10 -3 Pa; the reducing gas in step S2 is a mixture of carbon monoxide and argon in a volume ratio of 3:17; the amplitude of the ultrasonic vibration system in step S2 is 15 μm, the frequency is 20 kHz, and the power is 2 kW; the mass ratio of Ti, Mg, and Zr in the titanium magnesium zirconium deoxidizer in step S2 is 3:1:0.5; the addition amount of the titanium magnesium zirconium deoxidizer in step S2 is 0.06% of the mass of the copper material; the covering thickness of the composite deoxidizer in step S2 is 190 mm; the composite deoxidizer in step S2 comprises the following components in parts by weight: 88 parts of calcined charcoal, 6.5 parts of calcium fluoride, 4 parts of calcium oxide, 1.5 parts of boron oxide, and 2 parts of calcium boride.
[0038] The mass ratio of the composite refining agent, red phosphorus, phosphorus-copper master alloy, and copper liquid in step S3 is 0.015:0.03:0.02:100; the mass percentage concentration of phosphorus in the phosphorus-copper master alloy in step S3 is 13%; the composite refining agent in step S3 includes the following components in parts by weight: 3 parts of mixed rare earth, 0.45 parts of boron powder, 0.2 parts of magnesium, and 5 parts of calcium fluoride; the mixed rare earth is neodymium, yttrium, cerium, and lanthanum in a mass ratio of 6.5 :3:2:4 mixture; the magnetic field strength of the pulsed magnetic field in step S3 is 5T, the pulse frequency is 10Hz, and the duty cycle is 60%; the upper temperature of the gradient cooling zone in step S4 is 1180℃, and the lower temperature is 1050℃; the cooling rate is maintained at 18℃ / min; the crystallizer of the bottom-draw continuous casting machine in step S4 is made of a water-cooled copper mold, the crystallizer water pressure is 0.32MPa, and the cooling water flow rate is 10m³ / h. Example 4
[0039] A method for preparing oxygen-free copper comprises the following steps: Step S1, raw material pretreatment: placing the electrolytic copper raw material in a vacuum baking furnace for preheating for 1.8 hours to remove adsorbed water and volatile impurities; taking it out and cooling it to room temperature, sandblasting the surface oxide layer, ultrasonically cleaning it with ethanol, and then drying it with nitrogen to obtain the copper material; Step S2, gradient melting and deoxidation: in a reducing gas atmosphere, add the copper material to a graphite crucible and heat it to 1215°C at a rate of 7.5°C / min to melt; after it is completely melted, start the ultrasonic vibration system and add titanium magnesium zirconium deoxidizer at the same time, and ultrasonic vibration deoxidize for 38 minutes. During the vibration process, argon gas with a flow rate of 5.5L / min is introduced simultaneously; then the composite deoxidizer is covered, and argon gas with a flow rate of 19L / min is blown to strengthen deoxidation for 19 minutes; finally, the copper material is transferred to a holding furnace at 1190°C and argon gas with a flow rate of 4L / min is introduced. Deoxygenation was performed again for 28 min; Step S3, gradient refining treatment: After deoxidation, a composite refining agent is added to the copper liquid, and the copper liquid is refined at 1140°C for 14 minutes. Then, red phosphorus is added and the copper liquid is refined at 1155°C for 11 minutes. Finally, the temperature is lowered to 1105°C, a phosphorus-copper master alloy is added, and a pulsed magnetic field is applied. The copper liquid is further refined for 7.5 minutes, and then the slag is skimmed and filtered using a ceramic filter. Step S4, directional solidification casting: Directional solidification casting is performed using a bottom-draw continuous casting machine, with the molten copper passing through a water-cooled copper mold at a speed of 115 mm / min. A gradient cooling zone is set in the mold to achieve directional growth of columnar crystals, thereby obtaining an oxygen-free copper ingot; Step S5, heat treatment: placing the oxygen-free copper ingot into an annealing furnace, heating it to 540° C. at a heating rate of 4.5° C. / min under nitrogen protection, keeping the temperature for 2.5 hours, and then cooling it to room temperature along with the furnace.
[0040] The purity of the electrolytic copper raw material in step S1 is ≥99.99%; the preheating temperature in step S1 is 253°C and the vacuum degree is 1×10 -3 Pa; the reducing gas in step S2 is a mixture of carbon monoxide and argon in a volume ratio of 3:17; the amplitude of the ultrasonic vibration system in step S2 is 15.5 μm, the frequency is 20.5 kHz, and the power is 2.5 kW; the mass ratio of Ti, Mg, and Zr in the titanium magnesium zirconium deoxidizer in step S2 is 3:1:0.5; the addition amount of the titanium magnesium zirconium deoxidizer in step S2 is 0.065% of the mass of the copper material; the covering thickness of the composite deoxidizer in step S2 is 195 mm; the composite deoxidizer in step S2 comprises the following components in parts by weight: 89 parts of calcined charcoal, 7.5 parts of calcium fluoride, 4.5 parts of calcium oxide, 1.8 parts of boron oxide, and 2.5 parts of calcium boride.
[0041] The mass ratio of the composite refining agent, red phosphorus, phosphorus-copper master alloy, and copper liquid in step S3 is 0.018:0.03:0.02:100; the mass percentage concentration of phosphorus in the phosphorus-copper master alloy in step S3 is 14%; the composite refining agent in step S3 includes the following components in parts by weight: 3.5 parts of mixed rare earth, 0.55 parts of boron powder, 0.25 parts of magnesium, and 5.5 parts of calcium fluoride; the mixed rare earth is neodymium, yttrium, cerium, and lanthanum in a mass ratio of 7.5: 3.5:2.5:4.5 mixture; the magnetic field strength of the pulsed magnetic field in step S3 is 5T, the pulse frequency is 10 Hz, and the duty cycle is 60%; the upper temperature of the gradient cooling zone in step S4 is 1180°C, and the lower temperature is 1050°C; the cooling rate is maintained at 19°C / min; the crystallizer of the bottom-draw continuous casting machine in step S4 is made of a water-cooled copper mold, the crystallizer water pressure is 0.33 MPa, and the cooling water flow rate is 10.5 m³ / h. Example 5
[0042] A method for preparing oxygen-free copper comprises the following steps: Step S1, raw material pretreatment: placing the electrolytic copper raw material in a vacuum baking furnace for preheating for 2 hours to remove adsorbed water and volatile impurities; taking it out and cooling it to room temperature, sandblasting the surface oxide layer, ultrasonically cleaning it with ethanol, and then drying it with nitrogen to obtain the copper material; Step S2, gradient melting and deoxidation: In a reducing gas atmosphere, the copper material is added to a graphite crucible and heated to 1220°C at 8°C / min to melt; after complete melting, the ultrasonic vibration system is started, and a titanium magnesium zirconium deoxidizer is added at the same time, and ultrasonic vibration deoxidation is carried out for 40 minutes, and argon gas with a flow rate of 6 L / min is introduced during the vibration process; then, the composite deoxidizer is covered, and argon gas with a flow rate of 20 L / min is blown from the bottom to enhance deoxidation for 20 minutes; finally, the copper material is transferred to a holding furnace at 1200°C, and CO2 with a flow rate of 5 L / min is introduced for further deoxidation for 30 minutes; Step S3, gradient refining treatment: After deoxidation, a composite refining agent is added to the copper liquid, and the copper liquid is refined at 1150°C for 15 minutes. Then, red phosphorus is added and the copper liquid is refined at 1160°C for 12 minutes. Finally, the temperature is lowered to 1110°C, a phosphorus-copper master alloy is added, and a pulsed magnetic field is applied. The copper liquid is further refined for 8 minutes, and then the slag is skimmed and filtered using a ceramic filter. Step S4, directional solidification casting: Directional solidification casting is performed using a bottom-draw continuous casting machine, with the molten copper passing through a water-cooled copper mold at a speed of 120 mm / min. A gradient cooling zone is set in the mold to achieve directional growth of columnar crystals, thereby obtaining an oxygen-free copper ingot; Step S5, heat treatment: placing the oxygen-free copper ingot into an annealing furnace, heating it to 550° C. at a heating rate of 5° C. / min under nitrogen protection, keeping the temperature for 3 hours, and then cooling it to room temperature along with the furnace.
[0043] The purity of the electrolytic copper raw material in step S1 is ≥99.99%; the preheating temperature in step S1 is 255°C and the vacuum degree is 1×10 -3 Pa; the reducing gas in step S2 is a mixture of carbon monoxide and argon in a volume ratio of 3:17; the amplitude of the ultrasonic vibration system in step S2 is 16 μm, the frequency is 20.5 kHz, and the power is 3 kW; the mass ratio of Ti, Mg, and Zr in the titanium magnesium zirconium deoxidizer in step S2 is 3:1:0.5; the addition amount of the titanium magnesium zirconium deoxidizer in step S2 is 0.07% of the mass of the copper material; the covering thickness of the composite deoxidizer in step S2 is 200 mm; the composite deoxidizer in step S2 includes the following components in parts by weight: 90 parts of calcined charcoal, 8 parts of calcium fluoride, 5 parts of calcium oxide, 2 parts of boron oxide, and 3 parts of calcium boride.
[0044] The mass ratio of the composite refining agent, red phosphorus, phosphorus-copper master alloy, and copper liquid in step S3 is 0.02:0.03:0.02:100; the mass percentage concentration of phosphorus in the phosphorus-copper master alloy in step S3 is 15%; the composite refining agent in step S3 comprises the following components, in parts by weight: 4 parts of mixed rare earth, 0.6 parts of boron powder, 0.3 parts of magnesium, and 6 parts of calcium fluoride; the mixed rare earth is a mixture of neodymium, yttrium, cerium, and lanthanum in a mass ratio of 8:4:3:5; the magnetic field strength of the pulsed magnetic field in step S3 is 5 T, the pulse frequency is 10 Hz, and the duty cycle is 60%; the upper temperature of the gradient cooling zone in step S4 is 1180° C., and the lower temperature is 1050° C.; the cooling rate is maintained at 20° C. / min; the crystallizer of the bottom-draw continuous casting machine in step S4 is made of a water-cooled copper mold, the crystallizer water pressure is 0.35 MPa, and the cooling water flow rate is 11 m³ / h.
[0045] Comparative Example 1 This example provides a method for preparing oxygen-free copper, which is basically the same as Example 1, except that the ultrasonic vibration system is not started in step S2; an equal amount of calcined charcoal is used instead of boron oxide; and an equal amount of cerium is used instead of mixed rare earth.
[0046] Comparative Example 2 This example provides a method for preparing oxygen-free copper, which is basically the same as Example 1, except that no pulsed magnetic field is applied in step S3; an equal amount of calcined charcoal is used instead of calcium boride; and an equal amount of lanthanum is used instead of mixed rare earth.
[0047] In order to further illustrate the beneficial technical effects of the preparation methods of oxygen-free copper involved in each embodiment of the present invention, the oxygen-free copper prepared by the preparation methods of oxygen-free copper involved in Examples 1-5 and Comparative Examples 1-2 was subjected to composition analysis and related performance tests. The test results are shown in Table 1. The test method is as follows: (1) Oxygen content detection: Oxygen is measured by infrared absorption method, with reference to GB / T 5121.8-2008 Chemical analysis methods of copper and copper alloys Part 8: Determination of oxygen content; (2) Conductivity: Refer to GB / T 351-2019, test using the four-probe method, test temperature 20±0.5℃.
[0048] (3) Heat resistance: After each sample was subjected to a continuous high-temperature treatment at 900°C for 60 minutes, the changes in the average grain size before and after the continuous high-temperature treatment were measured and compared. The heat resistance was measured by the growth rate of the average grain size. The larger the value, the worse the heat resistance.
[0049] (4) Tensile strength: Refer to GB / T 228.1-2021 for tensile test.
[0050] Table 1
[0051] As can be seen from Table 1, the oxygen-free copper prepared by the preparation methods of oxygen-free copper according to the embodiments of the present invention has higher mechanical properties, heat resistance, and electrical conductivity than the comparative example product, and has a lower oxygen content. The combined use of an ultrasonic vibration system, a pulsed magnetic field, boron oxide, mixed rare earths, and calcium boride is beneficial in improving the above-mentioned properties.
[0052] The above embodiments are only for illustrating the technical concept and features of the present invention. Their purpose is to enable people familiar with this technology to understand the content of the present invention and implement it accordingly. They are not intended to limit the scope of protection of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing oxygen-free copper, characterized in that: The steps include: Step S1, raw material pretreatment: placing the electrolytic copper raw material in a vacuum baking furnace for preheating for 1-2 hours to remove adsorbed water and volatile impurities; taking it out and cooling it to room temperature, sandblasting the surface oxide layer, ultrasonically cleaning it with ethanol, and then drying it with nitrogen to obtain the copper material; Step S2, gradient melting and deoxidation: in a reducing gas atmosphere, add the copper material to a graphite crucible and melt it at 1200-1220°C at a rate of 5-8°C / min; after it is completely melted, start the ultrasonic vibration system and add titanium magnesium zirconium deoxidizer at the same time, and ultrasonic vibration deoxidize for 30-40 minutes. During the vibration process, argon gas with a flow rate of 4-6 L / min is introduced simultaneously; then cover the composite deoxidizer, and bottom blow argon gas with a flow rate of 15-20 L / min to strengthen deoxidation for 15-20 minutes; finally, transfer it to a holding furnace at 1150-1200°C and introduce argon gas with a flow rate of 1-5 L / min. Deoxygenate again for 20-30 minutes; Step S3, gradient refining treatment: After deoxidation, a composite refining agent is added to the copper liquid, and the copper liquid is refined at 1100-1150°C for 10-15 minutes. Then, red phosphorus is added and the copper liquid is refined at 1140-1160°C for 8-12 minutes. Finally, the temperature is lowered to 1090-1110°C, a phosphorus-copper master alloy is added, and a pulsed magnetic field is applied. The copper liquid is further refined for 5-8 minutes, and then the slag is skimmed and filtered using a ceramic filter. Step S4, directional solidification casting: Directional solidification casting is performed using a bottom-draw continuous casting machine, with the molten copper passing through a water-cooled copper mold at a speed of 100-120 mm / min. A gradient cooling zone is set in the mold to achieve directional growth of columnar crystals, thereby obtaining an oxygen-free copper ingot; Step S5, heat treatment: placing the oxygen-free copper ingot into an annealing furnace, heating it to 450-550° C. at a heating rate of 3-5° C. / min under nitrogen protection, keeping the temperature for 1-3 hours, and then cooling it to room temperature along with the furnace.
2. The method for preparing oxygen-free copper according to claim 1, wherein The purity of the electrolytic copper raw material in step S1 is ≥99.99%; the preheating temperature in step S1 is 240-255°C, and the vacuum degree is 1×10 -3 Pa.
3. The method for preparing oxygen-free copper according to claim 1, wherein The reducing gas in step S2 is a mixture of carbon monoxide and argon in a volume ratio of 3:17; the amplitude of the ultrasonic vibration system in step S2 is 14-16 μm, the frequency is 19.5-20.5 kHz, and the power is 1-3 kW.
4. The method for preparing oxygen-free copper according to claim 1, wherein The mass ratio of Ti, Mg and Zr in the titanium magnesium zirconium deoxidizer in step S2 is 3:1:0.5; the addition amount of the titanium magnesium zirconium deoxidizer in step S2 is 0.05-0.07% of the mass of the copper material.
5. The method for preparing oxygen-free copper according to claim 1, wherein The coating thickness of the composite deoxidizer in step S2 is 180-200 mm; the composite deoxidizer in step S2 comprises the following components in parts by weight: 85-90 parts of calcined charcoal, 5-8 parts of calcium fluoride, 3-5 parts of calcium oxide, 1-2 parts of boron oxide, and 1-3 parts of calcium boride.
6. The method for preparing oxygen-free copper according to claim 1, wherein: The mass ratio of the composite refining agent, red phosphorus, phosphorus-copper master alloy, and copper liquid in step S3 is (0.01-0.02):0.03:0.02:100; the mass percentage concentration of phosphorus in the phosphorus-copper master alloy in step S3 is 10-15%.
7. The method for preparing oxygen-free copper according to claim 1, wherein: The composite refining agent in step S3 includes the following components in parts by weight: 2-4 parts of mixed rare earth, 0.3-0.6 parts of boron powder, 0.1-0.3 parts of magnesium, and 4-6 parts of calcium fluoride.
8. The method for preparing oxygen-free copper according to claim 7, wherein: The mixed rare earth is prepared by mixing neodymium, yttrium, cerium and lanthanum in a mass ratio of (5-8):(2-4):(1-3):(3-5).
9. The method for preparing oxygen-free copper according to claim 1, wherein: The magnetic field intensity of the pulsed magnetic field in step S3 is 5 T, the pulse frequency is 10 Hz, and the duty cycle is 60%.
10. The method for preparing oxygen-free copper according to claim 1, wherein: The upper temperature of the gradient cooling zone in step S4 is 1180°C, and the lower temperature is 1050°C; the cooling rate is maintained at 15-20°C / min; the crystallizer of the bottom-draw continuous casting machine in step S4 is made of a water-cooled copper mold, the crystallizer water pressure is 0.28-0.35MPa, and the cooling water flow rate is 9-11m³ / h.
Citation Information
Patent Citations
An oxygen-free copper material, an oxygen-free copper material product, and a method for preparing the same.
CN114150179B
High-purity high-conductivity oxygen-free copper rod and processing method thereof
CN106180616A
Method for preparing oxygen-free copper bars
CN109465414A
Preparation method of high-purity oxygen-free copper
CN117587251A
Preparation method of dispersion copper refining impurity removal agent
CN119506589A